Multipartite entanglement dynamics in a cavity. (13th May 2015) - Amaro, J G; Pineda, C
Abstract: We study the dynamics of two kinds of entanglement and their interplay. On one hand, we consider the intrinsic entanglement within a central system composed of three two-level atoms and measured by multipartite concurrence; on the other, we consider the entanglement between the central system and a cavity, acting as an environment and measured with purity. Using dipole-dipole and Ising interactions between atoms, we propose two Hamiltonians: one homogeneous and one quasi-homogeneous. We find an upper bound for concurrence as a function of purity, associated with the evolution of the W state. A lower bound is also observed for the homogeneous case. In both situations, we show the existence of critical values of the interaction, for which the dynamics of entanglement seem complex.